Assessment Of Students’ Attitude And Utilisation Of Blendspace For Learning In National Open University Of Nigeria, Kwara State Study Centers - Ahmed Idris ISSA,; Joy Abosede eter; Taiwo Joshua Komolafe; Atanda Falade Ayotunde, (International Journal of Instructional Technology and Educational Studies)
This study aimed to assess students' attitude and utilization of Blendspace for learning in National Open University of Nigeria (NOUN) study centers. The research instrument was a researcher's designed questionnaire. A total of 342 NOUN students were sampled out of the 2,095 from the three centers. Statistical analysis and interpretation of the data obtained through the questionnaire were carried using Statistical Product and Service Solutions (SPSS) software program using descriptive and inferential statistics. The findings of the study revealed that the majority of the selected undergraduates had a positive attitude towards the integration of Information and Communication Technology (ICT) for learning, emphasizing its relevance to academic needs. Students who recognized the platform's relevance to their academic needs and embraced self-directed learning exhibited more frequent and in-depth utilization, utilizing resources to supplement classroom learning and explore topics beyond the curriculum. This study has shed light on the attitudes and utilization patterns of students towards blended learning in Kwara State study centers. The study recommends the Implementation of initiatives to promote positive attitudes toward ICT tools, support self-directed learning and enhance awareness of Blendspace benefits to optimize its utilization and foster an effective learning environment in NOUN study centers in Kwara State